Oscillating Bodies Understanding Tunisian Society through its Novels (1956-2011) - Pardey, Charlotte (Literaturen im Kontext. arabisch - persisch - türkisch, 2022)
Oscillating Bodies reads together the depiction of human bodies in arabophone and francophone Tunisian novels. This produces an understanding of Tunisian society from the country's independence in 1956 until the revolutionary upheavals of 2010/2011. It appears as a society that oscillates between the poles of tradition and modernity as well as various cultural influences. Oscillating Bodies also forms and can be read as an introduction to the Tunisian novel that is otherwise ignored by international literary studies.